Phosphodiesterase 3A expression is modulated by nitric oxidie in rat pulmonary artery smooth muscle cell - Busch, Cornelius; Graveline, A. R.; Jiramongkolchai, K.; Liu, H.; Sanchez, L. S.; Bloch, K. D. (Journal of physiology and pharmacology, 2010)
Phosphodiesterases (PDEs) limit vasodilation in response to a variety of signaling cascades by metabolizing the cyclic nucleotides cAMP and cGMP. The objective of this study was to test the hypothesis that NO regulates expression of PDE3A, a cGMP-inhibited PDE. Incubation of rat pulmonary artery smooth muscle cells (rPaSMCs) with the NO-donor compound S-nitroso-glutathione (GSNO) increased PDE3A gene expression in a dose- and time-dependent manner. NO-donors increased PDE3A protein levels. Total and milrinone inhibitable cAMP PDE activity were increased 2.8±0.1- and 2.0±0.1-fold respectively in extracts of rPaSMCs exposed to GSNO. The effects of GSNO on PDE3A gene expression were mimicked by the soluble guanylate cyclase (sGC) activators YC-1 and BAY 41-2272 and blocked by the sGC inhibitor ODQ. Incubation of rPaSMC with interleukin-1β and tumor necrosis factor-α induced PDE3A gene expression, an effect which was inhibited by L-NIL, an antagonist of NO synthase 2, or ODQ. Actinomycin D, an inhibitor of RNA polymerase, blocked the GSNO-induced increase of PDE3A mRNA levels, whereas cycloheximide, an inhibitor of protein translation, did not. These observations suggest that NO modulates PDE3A gene expression via mechanisms dependent upon cGMP synthesis and gene transcription. Prolonged exposure to NO may alter the sensitivity of vascular smooth muscle to cGMP- or cAMP-dependent vasodilators, as well as PDE isoform-selective inhibitors.